Move-Step Structure of Engineering and Non-engineering Students’ Final Project Report Background - Febryanto, Mohammad; Bakhti, Krisna Yudha; Sulyaningsih, Iis; Yuliah, Siti (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2024)
The quality of the research background provides readers with the essential context needed to understand the research problem. Therefore, it is crucial to enhance the quality of this section. This study investigates the comparison of the Move and Step structures between engineering and non-engineering students’ final project report background using Swales’ (2012) Create a Research Space (CARS) Move/Step analysis model. Data were collected from 71 students’ final project reports at a polytechnic in Bandung, comprising 35 from engineering fields and 36 from non-engineering fields. The results indicate that both fields incorporate Move 1, Move 2, and Move 3. In Move 1, both fields use Step 2 (Making topic Generalization) to establish a research area. Meanwhile, in Move 2, step 2 (Indicating a Gap) and step 4 (Continuing a Tradition) are frequently applied in non-engineering fields to establish a research niche. In Move 3, both fields use step 1A (Outlining Purposes) to describe their studies. The findings suggest no significant difference in the Move and Step structures between engineering and non-engineering fields. These insights may contribute to improving the quality of students’ final project reports.